2002
DOI: 10.1126/science.1069504
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cingulate: Single Neuronal Signals Related to Degree of Reward Expectancy

Abstract: As monkeys perform schedules containing several trials with a visual cue indicating reward proximity, their error rates decrease as the number of remaining trials decreases, suggesting that their motivation and/or reward expectancy increases as the reward approaches. About one-third of single neurons recorded in the anterior cingulate cortex of monkeys during these reward schedules had responses that progressively changed strength with reward expectancy, an effect that disappeared when the cue was random. Alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
315
4
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 469 publications
(353 citation statements)
references
References 39 publications
27
315
4
3
Order By: Relevance
“…Therefore, activation of the cingulate might be expected if subjects linked the alcohol cues with positive expectations of alcohol use. It has been reported that anterior cingulate activation may be related to the expectancy of reward and in our situation, expectancy to consume alcohol (Shidara and Richmond, 2002).…”
Section: Discussionmentioning
confidence: 56%
“…Therefore, activation of the cingulate might be expected if subjects linked the alcohol cues with positive expectations of alcohol use. It has been reported that anterior cingulate activation may be related to the expectancy of reward and in our situation, expectancy to consume alcohol (Shidara and Richmond, 2002).…”
Section: Discussionmentioning
confidence: 56%
“…The ERN (or, more generally, the response negativity, or RN) is a medial-frontally distributed component of the event-related brain potential (ERP) that is related to performance monitoring. It is elicited most prominently approximately 60-100 ms after subjects execute erroneous responses in choice response time tasks (Falkenstein, 1990;Gehring, Goss, Coles, Meyer, & Donchin, 1993) and appears to have its source in the anterior cingulate cortex (ACC; Dehaene, Posner, & Tucker, 1994;Gehrin & Willoughby, 2002;Holroyd, Dien, & Coles, 1998;Holroyd, Larsen, & Cohen, 2004), an area that is sensitive to reward and error information (Amador, Schlag-Rey, & Schlag, 2000;Shidara & Richmond, 2002) and is involved in the neuropathology of schizophrenia (Benes, Majocha, Bird, & Marotta, 1987;Benes, McSparren, Bird, SanGiovanni, & Vincent, 1991). A related ERP component, the feedback negativity (FBN), is observed when participants receive feedback about erroneous responding or poor outcomes and has also been localized to the ACC (Gehring & Willoughby, 2002;Miltner, Braun, & Coles, 1997;Ruchsow, Grothe, Spitzer, & Kiefer, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The frontal zones involved in craving seem to be the anterior cingulate cortex, orbitofrontal cortex, dorsolateral prefrontal cortex, and the inferior frontal gyrus (Grant et al, 1996;Bonson et al, 2002). The 7 anterior cingulate cortex, a brain area related to self-control (Tang et al, 2015) and to rewardrelated cognitive processes (Shidara and Richmond, 2002) has been found to be active when drug-related cues are presented (Filbey et al, 2009;Myrick et al, 2004). Activity in the anterior cingulum seems to act as a predecessor of the onset of craving, being linked to the emotional response triggered by drug-related cues (Robbins et al, 2008;Wexler et al, 2001).…”
mentioning
confidence: 99%